2010
DOI: 10.1016/j.virol.2009.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune response to H3N2 and H1N1 influenza virus infection in a human lung organ culture model

Abstract: We studied cytokine responses to influenza virus PR8 (H1N1) and Oklahoma/309/06 (OK/06, H3N2) in a novel human lung tissue model. Exposure of the model to influenza virus rapidly activated the mitogen activated protein kinase signaling (MAPK) pathways ERK, p38 and JNK. In addition, RNase protection assay demonstrated the induction of several cytokine and chemokine mRNAs by virus. This finding was reflected at the translational level as IL-6, MCP-1, MIP-1α/β, IL-8 and IP-10 proteins were induced as determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 43 publications
(46 reference statements)
5
73
0
Order By: Relevance
“…It has already been shown that human lung slices exposed to live influenza virus induce a strong pro-inflammatory cytokine and chemokine response. 15 This response included induction of IL-6 and IFNg, monocyte chemokines MIP-1a/b and MCP-1, the neutrophil chemokine IL-8 and the lymphocyte chemokine IP-1. 15 Immunohistochemistry data showed that macrophages and alveolar epithelial cells were responsible for production of these soluble mediators.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has already been shown that human lung slices exposed to live influenza virus induce a strong pro-inflammatory cytokine and chemokine response. 15 This response included induction of IL-6 and IFNg, monocyte chemokines MIP-1a/b and MCP-1, the neutrophil chemokine IL-8 and the lymphocyte chemokine IP-1. 15 Immunohistochemistry data showed that macrophages and alveolar epithelial cells were responsible for production of these soluble mediators.…”
Section: Discussionmentioning
confidence: 99%
“…15 This response included induction of IL-6 and IFNg, monocyte chemokines MIP-1a/b and MCP-1, the neutrophil chemokine IL-8 and the lymphocyte chemokine IP-1. 15 Immunohistochemistry data showed that macrophages and alveolar epithelial cells were responsible for production of these soluble mediators. To assess if this would apply to a vaccine antigen, we incubated PCLS with a seasonal influenza vaccine and tetanus toxin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The structural integrity of lung tissue is maintained (31), and this allows for cell-cell interactions in a more complex and native three-dimensional system. We (42) adapted this model to study cytokine responses to influenza virus in the human lung. Detailed mech-anistic studies of intracellular processes such as signal pathway activation can be examined in human tissue without risk to the host.…”
mentioning
confidence: 99%